Antioxidant and Hepatoprotective Activities of b-N-Cyanoethyl Acyl Hydrazides Derivatives - Shujaat, S.; Makhmoor, T.; Naheed, S.; Choudhary, M.I. (Asian Journal of Chemistry, 2010)
In the present study, b-N-cyanoethyl acyl hydrazides derivatives 1-9 were investigated for antioxidant and hepatoprotective properties. Compounds 2, 3, 5-8 exhibited significant free radical scavenging activities against 1,1-diphenyl-2-picrylhydrazyl radicals, while rest of the compounds 1, 4 and 9 have shown moderate activities. Hepatoprotective activity of these compounds was investigated in carbon tetrachloride induced liver toxicity model. Animals were pretreated at a dose level of 10 mg/Kg body weight before the injection of carbon tetrachloride and serium was analyzed after 48 h of carbon tetrachloride induced hepatotoxicity model in Wistar rats. Results showed that the levels of serum biochemical parameters sAST, sALT and bilirubins were largely maintained (p < 0.05) by most of the compounds (3-6 and 8) as compared to pathological control. In conclusion these b-N-cyanoethyl acyl hydrazides derivatives showed both antioxidant and hepatoprotective potential.